An in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings
By spraying the NiAl buffer layer and the 8YSZ reinforcement layer on the surface of the ceramic layer of the thermal barrier coating, combined with the three-point bending experiment of the digital image correlation method, the problem that the prior art cannot characterize the interface fracture toughness of the thermal barrier coating at high temperatures is solved, and accurate characterization and testing in high temperature environments are achieved.
Patent Information
- Application Number
- CN202411919297.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art cannot effectively characterize the interface fracture toughness of thermal barrier coatings under high temperature conditions, resulting in the inability to accurately evaluate its performance in high temperature environments.
A hybrid reinforcement layer was used, including spraying NiAl as a buffer layer on the surface of the ceramic layer and spraying 8YSZ as a reinforcement layer on the surface of the buffer layer. A three-point bending experiment was conducted in combination with the digital image correlation method, and the critical energy release rate and stress intensity factor of the interface were recorded and calculated in real time to achieve in-situ characterization of the fracture toughness of the high-temperature interface of the thermal barrier coating.
The accurate characterization of the interface fracture toughness of the thermal barrier coating under high temperature environment is achieved. The test data is real-time and accurate, the test period is short, and the spraying of the mixed reinforcement layer has less impact on the sample to be tested and the residual stress is smaller.
Smart Images

Figure CN119354736B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of performance analysis of coating materials, and particularly relates to an in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings, which realizes high-temperature interface fracture toughness analysis of materials by means of their chemical or physical properties. Background Art
[0002] Gas turbine blades are mainly made of high-temperature resistant nickel-based alloy materials, which have high temperature (>1000℃) performance. The current service temperature of gas turbine blades is close to 90% of the melting point of the alloy material, and there is very limited room for further increasing the service temperature. The use of thermal barrier coating technology can reduce the surface temperature of metal parts in high-temperature environments and improve thermal efficiency. However, due to the extremely harsh service environment of thermal barrier coatings, especially the ceramic layer is simultaneously facing the impact of high-speed particles and chemical corrosion, it is very easy to fail and peel off.
[0003] Among them, cracks generated at the interface of thermal barrier coatings under the action of mechanical and thermal coupling are one of the main failure modes of thermal barrier coatings. The interfacial fracture toughness of thermal barrier coatings represents the ability of thermal barrier coatings to hinder the expansion of their own interfacial cracks, and is an important property of thermal barrier coatings. The bending test can characterize the interfacial bonding performance of thermal barrier coatings, but the characterization of interfacial fracture toughness of thermal barrier coatings always remains at room temperature. This is because the characterization method of room temperature interfacial fracture toughness cannot be carried out at high temperatures. For example, the bonding strength of high-temperature glue is much lower than that of room temperature glue, resulting in the inability to carry out the three-point bending method for characterizing interfacial fracture toughness at high temperatures. For another example, the three-point bending test can measure the interfacial fracture toughness of thermal barrier coatings at room temperature, but at high temperatures, the interfacial fracture toughness of thermal barrier coatings can no longer be characterized due to the change in the propagation model of the surface and interfacial cracks of the thermal barrier coating. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an in-situ characterization method for the high-temperature interface fracture toughness of thermal barrier coatings, so as to solve the problem that the interface fracture toughness of thermal barrier coatings cannot be characterized under high temperature conditions. In the present invention, high temperature refers to 1000-1400°C.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] An in-situ characterization method for high-temperature interface fracture toughness of a thermal barrier coating comprises or consists of the following steps:
[0007] Step 1: Using a metal test piece with a thermal barrier coating as a test sample, spraying NiAl as a buffer layer on the surface of the ceramic layer in the thermal barrier coating, the function of the buffer layer is to construct a transition structure between the thermal barrier coating and the reinforcement layer.
[0008] Step 2, spraying a reinforcement layer on the surface of the buffer layer, wherein the buffer layer and the reinforcement layer form a mixed reinforcement layer.
[0009] Step 3: Use a three-point bending device with an in-situ observation function of a digital image correlation method to perform a three-point bending experiment on the sample to be tested with a hybrid reinforcement layer at a target high temperature of 1000-1400° C., and record the three-point bending process in real time.
[0010] Step 4: obtain the strain cloud map of the observation area by digital image correlation method, obtain parameters from the strain cloud map, and calculate the interface critical energy release rate of the three-point bending test and stress intensity factor , both of which are proportional to the high-temperature interface fracture toughness of the thermal barrier coating, that is, the critical energy release rate of the interface The larger the value, the greater the high-temperature interface fracture toughness of the thermal barrier coating. The larger the value is, the greater the high-temperature interface fracture toughness of the thermal barrier coating is. Thus, the in-situ characterization of the high-temperature interface fracture toughness of the thermal barrier coating can be achieved.
[0011] In the embodiment of the present invention, in step 1, NiAl with a thickness of 40-80 microns is sprayed on the surface of the ceramic layer using atmospheric plasma spraying technology as a buffer layer.
[0012] In the embodiment of the present invention, in step 2, 8YSZ with a thickness of 1-2 mm is sprayed on the surface of the buffer layer using atmospheric plasma spraying technology as a reinforcement layer.
[0013] In the embodiment of the present invention, in step 3, before the three-point bending test, a two-color speckle is coated on the surface of the sample to be tested.
[0014] In the embodiment of the present invention, the two-color speckle is black speckle and white speckle, the black speckle is a mixture of cobalt oxide powder and inorganic glue capable of withstanding high temperature, and the white speckle is aluminum oxide powder.
[0015] In the embodiment of the present invention, in the step 3, during the three-point bending test, after heating to the target high temperature, the temperature is kept constant for more than 10 minutes to ensure that the temperature of the sample to be tested with the mixed reinforcement layer is stable and uniform during the experiment.
[0016] In the embodiment of the present invention, in step 4, the parameters obtained from the strain cloud map are substituted into the following formula to calculate the interface critical energy release rate of the three-point bending test: and stress intensity factor :
[0017] Where P s and P eare the load values at the beginning and end of the three-point bending test, respectively, F is the load, is the deflection, F s is the initial load, F e is the load at the end, is the load F e The deflection under is the load F s Deflection under is the load F e To load F s The number of data points between and is the load corresponding to the i-th data point and the i+1-th data point, When the load is The deflection at When the load is The deflection at is the elastic modulus of the ceramic layer, is the elastic modulus of the bonding layer, is a dimensionless parameter, , µ1 and µ2 are the shear moduli of the two materials near the crack, v1 and v2 are the Poisson's ratios of the two materials near the crack, and the near the crack means that the distance from the crack is in the micrometer level; b is the width of the sample to be tested, a is the crack length caused by the three-point bending test, is the crack extension length.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. Through the hybrid reinforcement layer, a sufficiently large stress can be generated at the interface between the ceramic layer and the reinforcement layer when the bending deflection is small, so that the interface crack initiates and expands; the hybrid reinforcement layer has an appropriate thickness, which can make the interface crack away from the sample boundary, which is conducive to observing the strain state near the crack by digital image correlation method.
[0020] 2. The spraying of the mixed reinforcement layer has less impact on the sample to be tested and less residual stress. Since the hardness and elastic modulus of NiAl at high temperature are both low, when NiAl is sprayed onto the surface of the sample to be tested by atmospheric plasma spraying technology, the impact force of NiAl powder on the sample to be tested is small. The reinforcement layer is selected as 8YSZ, which has a low thermal expansion coefficient and generates less residual stress after cooling.
[0021] 3. The present invention can realize in-situ characterization of the interface fracture toughness of the thermal barrier coating in the high-temperature environment in which the thermal barrier coating is actually in service, and the test data can be obtained in real time and accurately, with a short test cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1It is a schematic diagram of the structure of the sample to be tested with a mixed reinforcement layer according to the present invention.
[0023] Figure 2 Schematic diagram of the expected crack extension of the sample during the experiment of the present invention.
[0024] Figure 3 It is a schematic diagram of the three-point bending model of the present invention.
[0025] Figure 4 for Figure 3 Schematic diagram of the partially equivalent cantilever beam in the dashed box.
[0026] Figure 5 The crack propagation process of the sample observed by the digital image correlation method in the high-temperature resistant hybrid reinforcement layer assisted three-point bending peeling method, where: (a) is the initial state; (b) the prefabricated crack on the surface of the thermal barrier coating penetrates the ceramic layer; (c) is the initiation of the interface crack; (d) is the substantial expansion of the interface crack.
[0027] Figure 6 The strain cloud diagram of the y-direction strain of the sample at different deflections observed by the digital image correlation method, where: (a) the deflection is 0; (b) the deflection increases, the prefabricated crack extends to the interface between the ceramic layer and the bonding layer, and the interface crack initiates; (c) the interface crack extends; (d) as the deflection increases, the interface crack continues to extend.
[0028] Figure 7 for Figure 3 The y-direction strain-time curve of the sample, where: (a) is Figure 3 (b) The strain-time curve in the y direction on the left side of the sample; Figure 3 Schematic diagram of the strain-time curve in the y direction on the right side of the sample.
[0029] Figure 8 Schematic diagram of the load-deflection curve from 25°C to 600°C.
[0030] Fig. 9 Schematic diagram of the interface fracture toughness of electron beam physical vapor deposition thermal barrier coatings from 25°C to 600°C. DETAILED DESCRIPTION
[0031] The embodiments of the present invention are described in detail below with reference to the accompanying drawings and examples.
[0032] In order to in-situ characterize the high-temperature interface fracture toughness of thermal barrier coatings, the present invention adopts the following main steps:
[0033] Step 1: Take a metal test piece with thermal barrier coating as the test sample, refer to Figure 1 As shown, NiAl is sprayed as a buffer layer 4 on the surface of the ceramic layer 3 in the thermal barrier coating.
[0034] In this step, atmospheric plasma spraying technology is used to spray NiAl with a thickness of 40-80 microns as a buffer layer 4, and the transition between the thermal barrier coating and the reinforcement layer 5 can play a buffering role through the buffer layer 4. Compared with NiCoCrAlY, NiAl has a lower thermal expansion coefficient, and the cooling shrinkage stress generated after atmospheric plasma spraying is smaller.
[0035] Step 2, after spraying the buffer layer 4, spray the reinforcement layer 5 on the surface of the buffer layer 4, the buffer layer 4 and the reinforcement layer 5 form a mixed reinforcement layer 7, and obtain a sample to be tested with a mixed reinforcement layer 7, such as Figure 1 As shown, it includes a substrate 1, a bonding layer 2, a ceramic layer 3, a buffer layer 4 and a reinforcement layer 5 arranged in sequence. The figure also shows a prefabricated crack 6, which is used to allow the crack tip to reach the ceramic layer 3, so that the stress is concentrated at the tip of the prefabricated crack 6 during the bending loading process, thereby preventing cracking between the ceramic layer 3 and the reinforcement layer 5.
[0036] Figure 2 The expected crack extension during the experiment is shown. When the sample is subjected to bending loading, the energy released by the brittle fracture of the ceramic layer 3 will cause cracks to form at the interface between the ceramic layer 3 and the bonding layer 2, which is the expected crack extension 8 in the figure.
[0037] The reinforcement layer 5 of the present invention needs excellent mechanical properties, and can be resistant to high temperatures, anti-oxidation, and has good bonding with NiAl. The material of the reinforcement layer 5 of this embodiment is 8YSZ, that is, yttria-stabilized zirconia. Specifically, atmospheric plasma spraying technology can be used to spray 8YSZ with a thickness of 1-2 mm on the surface of the buffer layer 4 as the reinforcement layer 5. From experience, 8YSZ with a thickness of 1 mm can provide a sufficiently large stress to cause cracks to form at the interface between the buffer layer 4 and the reinforcement layer 5 when bent. And 1mm is also enough to prevent the interface crack from being too close to the edge of the sample, reducing the effect of digital image correlation (DIC) observation under high temperature conditions.
[0038] Step 3, using a three-point bending device with an in-situ observation function of a digital image correlation method, a three-point bending experiment is performed on the sample to be tested with the hybrid reinforcement layer 7 at a target high temperature, and the three-point bending process is recorded in real time. In the present invention, the target high temperature is 1000-1400°C, and is set to 1200°C in the experiment.
[0039] During the three-point bending test in this step, after the temperature is raised to the target high temperature, the temperature is kept for more than 10 minutes to ensure that the temperature of the sample to be tested with the mixed reinforcement layer 7 is stable and uniform during the experiment. In addition, before the three-point bending test, a two-color speckle is coated on the surface of the sample to be tested with the mixed reinforcement layer 7. For example, the two-color speckle is a black speckle and a white speckle, wherein the black speckle can be a mixture of cobalt oxide powder and an inorganic glue that can withstand high temperatures, and the white speckle can be an aluminum oxide powder. Through the two-color speckle, the crack changes can be observed more clearly.
[0040] The three-point bending process of the sample to be tested with the hybrid reinforcement layer 7 can be recorded in real time by the digital image correlation system, and the process and path of crack propagation can be clearly seen in the figure.
[0041] Step 4: obtain the strain cloud map of the observation area by digital image correlation method, obtain parameters from the strain cloud map, and calculate the interface critical energy release rate of the three-point bending test and stress intensity factor .
[0042] The principle of this step can be described by the following theoretical model.
[0043] A typical three-point bending model is Figure 3 As shown, the crack 9 is shown in the figure. In the three-point bending, the present invention assumes that the sample to be tested with the mixed reinforcement layer 7 does not yield, and ignores the heat caused by loading. Then, the energy conservation law can be obtained:
[0044] in is the work done by the pressure head of the three-point bending device, is the elastic potential energy of the sample to be tested with the hybrid reinforcement layer 7, The energy released by the crack expansion. The work done by the indenter during the three-point bending process It can be expressed as:
[0045] Where P s and P e are the load values at the beginning and end of the three-point bending test, respectively. is the change in elastic potential energy of the sample to be tested with the hybrid reinforcement layer 7, and P s and P e Elastic potential energy corresponding to the load. When the ceramic layer 3 is separated from the bonding layer 2, the separated part is a free end and is no longer subject to bending moment and shear force. The three-point bending can be regarded as the pressure head as a fixed point, the two fulcrums push upward, and the fulcrum load is the pressure head load half of . Three-point bending side (i.e. Figure 3 The bending moment and shear force distribution of the cantilever beam are the same as those of the cantilever beam, so the side of the sample to be tested with the hybrid reinforcement layer 7 in the three-point bending test (i.e. Figure 3 The part in the dashed box in the middle) is regarded as a cantilever beam, and the right part of the cantilever beam (i.e. Figure 3 The load in the dashed box is the support load. The span of the three-point bending is set to L, so the total length of the cantilever beam is .for Figure 4 For the cantilever beam in the figure, assuming that the distance between a section and the fixed end is x, under small deformation, the deflection y of the section meets the equation:
[0046] The fixed end refers to the surface of the fixed point along the depth direction, and the small deformation refers to the small deformation assumption in material mechanics, that is, when the deformation of a component due to external force is much smaller than its original size, it is defined as a small deformation. In the above formula, M is the bending moment of the section, S is the stiffness of the section, , then:
[0047] Assuming that the crack length caused by the three-point bending test is a, there are different a for different unloading points, so the deflection at this time can be written as:
[0048] Ignoring the heat generated during unloading, the elastic potential energy in the sample with the hybrid reinforcement layer 7 is the work done to the outside during unloading. During virtual unloading, the virtual unloading point where the sample with the hybrid reinforcement layer 7 does work to the outside is set to be the same as the actual loading point. Since the interface crack will not expand or close during unloading, the potential energy during unloading is is a constant. The load at the support is F and the deflection is During the unloading process, the work done by the sample with the mixed reinforcement layer 7 on the outside world, that is, its elastic potential energy, is expressed as:
[0049] Assume that the load is from F s Increase to F e During the process, the interface crack expanded , then the interfacial energy release of the cantilever beam in this process is It can be expressed as:
[0050] Since the three-point bending is symmetrical, the total energy released by the interface fracture of the three-point bending is twice the energy released by its half side. The critical energy release of the interface of the three-point bending is for:
[0051] in, is the load F e The deflection under is the load F s Deflection below.
[0052] In particular, if no interface cracks are generated, the load-deflection curve should be a straight line during loading, and the result of the above formula is 0, that is, no energy is released due to crack extension. , here It refers to the interface crack extension length generated during the entire loading process, while It means F s Increase to F e The interface crack extension length. The energy released by the crack per unit area during the process, that is, the critical energy release rate of the interface in the three-point bending test It can be expressed as the following equation (1):
[0053] (1)
[0054] Where b is the width of the sample to be tested with the hybrid reinforcement layer.
[0055] Since the materials near the interface of thermal barrier coatings have mutually mismatched material properties, the stress and strain conditions of different materials near the interface will inevitably be different. This mismatch of stress and strain makes the interface crack propagation of thermal barrier coatings not a simple type I crack mode or type II crack mode. Therefore, a mixed crack mode is needed to describe it.
[0056] Assume that the two materials near the interface crack are isotropic materials, the elastic moduli of the two materials are E1 and E2 respectively; the Poisson's ratios of the two materials are v1 and v2 respectively; the shear moduli of the two materials are µ1=E1 / (2+2v1) and µ2=E2 / (2+2v2) respectively. In the present invention, near the crack means that the distance from the crack is in the micrometer level.
[0057] A pair of dimensionless parameters α and β are used to describe the elastic mismatch at the interface of two different materials:
[0058] Since the crack propagation at the sample interface in three-point bending belongs to a plane strain problem, , , j = 1, 2, respectively represent two materials, and the obtained α and β are:
[0059] The parameters α and β describe the difference in elastic properties of the two materials and the interface constraints between the materials.
[0060] The crack tip behavior at a bi-material interface can be described by its energy release rate and loading phase angle, which describes the degree of mixing of mode I and mode II crack modes. The energy release rate is defined as the reduction in potential energy associated with the crack volume, and it characterizes the load amplitude when the crack extends a unit area. The stress intensity factor K can be used I and K II To represent it, as follows:
[0061] when When the critical value of interface fracture toughness is reached, the crack will propagate. and K I and K II The corresponding stress intensity factors for the two crack modes are: , is the stress intensity factor of the thermal barrier coating interface in three-point bending, expressed as the following equation (2):
[0062] (2)
[0063] In the formula, is the load F e To load F s The number of data points between and is the load corresponding to the i-th data point and the i+1-th data point, When the load is The deflection at When the load is The deflection at is the elastic modulus of the ceramic layer 3, is the elastic modulus of the adhesive layer 2.
[0064] By processing the original image data using the digital image correlation method, a strain cloud map of the observation area can be obtained. From the strain cloud map, it can be seen that the digital image correlation method can capture the strain of the sample very well. According to the strain-time curve, the inflection point where the strain suddenly increases is found from the graph, and the corresponding moment is the moment when the crack reaches this point. Since this sudden change is very drastic, the change in the length of the crack can be accurately read from the strain-time curve at each position and the distance between each position. The interface crack extension length, load, deflection, and elastic modulus are input into equations (1) and (2) to obtain the critical energy release rate of the interface fracture of the thermal barrier coating. and stress intensity factor .
[0065] In a specific embodiment of the present invention, an electron beam physical vapor deposition thermal barrier coating is used as an experimental object. The substrate 1 of the thermal barrier coating is made of GH3536 nickel-based high-temperature alloy, the surface is polished with 800# sandpaper, the roughness is between 0.015 and 0.025 microns, and the thickness of the plate is 2.5 mm. Then it is cut into The bonding layer 2 is made of NiCoCrAlY sprayed by atmospheric plasma spraying, with a thickness of 0.1 mm, and the ceramic layer 3 is 0.2 mm thick and is made by electron beam evaporation coating process; the buffer layer 4 is 0.1 mm thick; the reinforcement layer 5 is 1.1 mm thick. After preparation, it is cut into strips with a width of 2.5 mm to obtain a sample with a length, width and thickness of 30 mm, 2.5 mm and 4 mm respectively, with a mixed reinforcement layer 7.
[0066] The three-point bending experiment was conducted using a three-point bending device with in-situ observation function using digital image correlation. The span of the three-point bending bracket was 24 mm; the heating rate of the high-temperature furnace was 10 °C / min; after reaching the target temperature of 1200 °C, the temperature was kept for 10 min to ensure that the temperature of the sample was stable and uniform during the experiment. After the sample surface was coated with a thin layer of two-color speckle, Figure 5 As shown in FIG. 1 , the three-point bending process of the sample to be tested with the hybrid reinforcement layer 7 is recorded in real time by the digital image correlation system. The process and path of crack propagation can be clearly seen in the figure. Figure 5 As shown in (a), the tip of the prefabricated crack is located in the ceramic layer 3. In the figure, IC represents the buffer layer 4, BC represents the bonding layer 2, and TC represents the ceramic layer 3. As the sample deflection increases, the prefabricated crack expands and reaches the interface between the ceramic layer 3 and the bonding layer 2, as shown in FIG. Figure 5 As shown in (b). Figure 5 As shown in (c) and (d), with the increase of deflection, the interface crack initiates and expands. The crack expansion process and the location of the interface crack on the sample can be clearly seen through the unprocessed original digital image correlation method image. By processing the original image data by digital image correlation method, the strain cloud map of the observation area can be obtained, as shown in Figure 1. Figure 6 As shown in (a), (b), (c) and (d), IC represents the buffer layer 4, BC represents the bonding layer 2, and TC represents the ceramic layer 3. It can be seen from the strain cloud diagram that the digital image correlation method can capture the strain of the sample very well.
[0067] The crack lengths shown in the original data graph and strain cloud graph of the digital image correlation method are relatively lagging. In order to accurately count the crack lengths at different times, a measurement point is selected every 0.2 mm at the location where the interface crack extends, where the origin is at the intersection of the straight line where the prefabricated crack is located and the interface crack. The strain-time curves in the y direction at different locations on the interface are as follows: Figure 7 As shown, a measurement point is selected every 0.2 mm. The figure shows 6 curves showing the data of 6 measurement points. Figure 7 As can be seen in (a) and (b), the strain will suddenly increase from a certain moment and an inflection point will appear. The inflection point corresponds to the time when the crack reaches the measurement point. The change in crack length can be accurately read from the strain-time curve and distance of each measurement point. The load-deflection curve of the sample at different temperatures is shown in Figure 1. Figure 8 As shown, the elastic modulus of the material at different temperatures can be obtained. In the present invention, the y direction refers to the load direction.
[0068] Inputting the relevant data into equations (1) and (2), the critical energy release rate and stress intensity factor of the interface fracture of the thermal barrier coating are obtained as follows: Fig. 9 As shown in the figure, it can be seen that when the temperature rises from 25°C to 600°C, the stress intensity factor of the interface decreases with the increase of temperature. This is because the increase of temperature will increase the atomic distance and vibration in the interface and weaken the interaction force between atoms. On the other hand, the energy release rate increases with the increase of temperature, and the increase amplitude increases slightly with the increase of temperature. Combined with the change of stress intensity factor, the final energy release rate is actually the result of the competition between the reduction of interatomic force and the increase of critical strain.
Claims
1. An in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings, characterized in that: The steps include: Step 1, using a metal test piece with a thermal barrier coating as a test sample, spraying NiAl with a thickness of 40-80 microns as a buffer layer on the surface of the ceramic layer in the thermal barrier coating using atmospheric plasma spraying technology; Step 2, using atmospheric plasma spraying technology to spray 8YSZ with a thickness of 1-2 mm as a reinforcement layer on the surface of the buffer layer, the buffer layer and the reinforcement layer form a mixed reinforcement layer; the prefabricated crack penetrates the buffer layer and the reinforcement layer, and the tip reaches the ceramic layer; Step 3, using a three-point bending device with a digital image correlation method in-situ observation function, a three-point bending experiment is performed on the sample to be tested with the hybrid reinforcement layer at a target high temperature, and the three-point bending process is recorded in real time; the target high temperature is 1000-1400° C.; Step 4: The strain cloud map of the observation area is obtained by digital image correlation method. The parameters are obtained from the strain cloud map and the critical energy release rate G of the interface in the three-point bending test is calculated by the following formula: c and stress intensity factor K C : Interface critical energy release rate G c The larger the value, the greater the high-temperature interface fracture toughness of the thermal barrier coating. C The larger it is, the greater the high-temperature interface fracture toughness of the thermal barrier coating is; Where P s and P e are the load values at the beginning and end of the three-point bending test, respectively. F is the load, δ is the deflection, and F s is the initial load, F e is the load at the end, δ e is the load F e The deflection under s is the load F s Deflection under load; n is the load F e To load F s The number of data points between i and F i+1 is the load corresponding to the i-th data point and the i+1-th data point, δ i When the load is F i The deflection at i+1 When the load is F i+1 The deflection at TC is the elastic modulus of the ceramic layer, E BC is the elastic modulus of the bonding layer, β is a dimensionless parameter, μ1 and μ2 are the shear moduli of the two materials near the crack, v1 and v2 are the Poisson's ratios of the two materials near the crack, and the near the crack refers to the distance from the crack in micrometers; b is the width of the sample to be tested, a is the crack length caused by the three-point bending test, and Δa is the crack extension length.
2. The in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings according to claim 1, characterized in that: In the step 3, before the three-point bending test, two-color speckle is coated on the surface of the sample to be tested.
3. The in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings according to claim 2, characterized in that: The two-color speckle is black speckle and white speckle, the black speckle is a mixture of cobalt oxide powder and inorganic glue, and the white speckle is aluminum oxide powder.
4. The in-situ characterization method for high-temperature interface fracture toughness of thermal barrier coatings according to claim 1, characterized in that: In the step 3, during the three-point bending test, after heating to the target high temperature, the temperature is kept constant for more than 10 minutes to ensure that the temperature of the sample to be tested with the mixed reinforcement layer is stable and uniform during the experiment.
Citation Information
Patent Citations
Method for measuring interface bonding strength of thermal barrier coating layer
CN107345898A
Test sample and test method for bonding strength of ceramic coating, and preparation method of test sample
CN110031330A